Hybrid organic-inorganic nanocomposites based on poly(hydroxyethyl methacrylate)/ silica (PHEMA/SIO2) - Mucci, Veronica Lujan (2013)
Hybrid organic-inorganic nanocomposites were prepared through the simultaneous polymerization of 2-hydroxyethyl methacrylate and tetraethoxysilane (TEOS) by the sol-gel process. The resulting PHEMA/SiO2 films (~ 1.5 mm thick) were rigid and optically transparent. The films were crushed into fine particles which were used as filler for light-cured dental composite resins based on methacrylate monomers. The presence of methacrylate groups in the PHEMA/SiO2 particles improves their compatibility with the methacrylate monomer used as matrix of the composite resins. This facilitates the incorporation of high amount of filler into the resins. The composites containing particles based on PHEMA/SiO2 offer the possibility of reduced polymerization shrinkage without severe reductions in flow characteristics of the prepolymerized resin. The amount of reinforcing filler in the final composite will be determined as a compromise between optimizing both the rheological properties and the volumetric shrinkage without jeopardizing the mechanical properties required by a particular application.